Secure Messaging, Diabetes Self‐Management, and the Importance of Patient Autonomy: A Mixed Methods Study. (20th August 2020) - Robinson, S.; Zocchi, M.; Netherton, D.; Ash, A.; Purington, C.; Am, L.; DeLaughter, K.; Shimada, S.
Abstract : Diabetes is a complex, chronic disease that requires patients' effective self‐management between clinical visits; this in turn relies on patient self‐efficacy. The support of patient autonomy from health care providers is associated with better self‐management and greater diabetes self‐efficacy. Effective provider‐patient secure messaging (SM) through patient portals may improve disease self‐management and self‐efficacy. SM that supports patients' sense of autonomy may mediate this effect by providing patients ready access to their health information and better communication with their clinical teams. We examined the association between health care team‐initiated SM and diabetes self‐management and self‐efficacy, and whether this association was mediated by patients' perceptions of autonomy support from their health care teams. We used health record information, SM coding, and surveys to conduct a mixed methods study (QUANT → qual). Using mediation analyses, this study estimated the relationship between clinical team‐initiated SM and patient‐reported measures (perceived autonomy, diabetes self‐management behaviors, and diabetes self‐efficacy) and examined the qualitative content of the messages. 446 Veterans, aged 18 and older with a diagnosis of diabetes who were sustained users of the VA's My HealtheVet patient portal, participated in the survey (response rate = 37%). We used stratified random sampling to select a sample of Veterans balanced on location (rural vs. urban), mental health status (mental health diagnoses vs. no comorbid mental health diagnoses), and blood glucose control (not in control vs. in control). Patients who received at least one proactive SM from their clinical team were significantly more likely to engage in better diabetes self‐management and report a higher sense of diabetes self‐efficacy. The relationship between proactive SM and diabetes self‐management was mediated by the patient's perception of autonomy support. Of all clinical team members, nurses were the most likely to proactively send a SM. The majority of proactive SM discussed scheduling, referrals, or other administrative content. Perceived autonomy support is important for diabetes self‐management and self‐efficacy. Patients whose clinical teams initiated at least one SM were significantly more likely to perceive their health care climate as more autonomy‐supportive compared to patients that did not receive a team‐initiated SM. Patients that perceived a more autonomy‐supportive health care climate were significantly more likely to report engaging in more diabetes self‐management behaviors and more likely to report a higher sense of diabetes self‐efficacy. Proactive communication from clinical teams to patients can help to foster a patient's sense of autonomy and encourage better diabetes self‐management and self‐efficacy. Effective communication between patients and their clinical teams is critical for the continued care of managing a complex, chronic condition such as diabetes. SM functionality available through patient portals such as My HealtheVet offers teams the opportunity to easily communicate with their patients, which can in turn support improvements in disease management and health outcomes. Department of Veterans Affairs.